2019
DOI: 10.1177/0308022619841320
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Management Pathways in Stroke Services (COMPASS): A qualitative investigation of key issues in relation to community stroke teams undertaking cognitive assessments

Abstract: Introduction: Cognitive problems are common after stroke and their identification and management is important for survivors, carers and clinicians. However, the appropriateness of the screening methods and ways in which results inform community clinical care have not been established. The aim of this phase of the Cognitive Management Pathways in Stroke Services study was to explore key issues to undertaking cognitive assessment, particularly in community settings. Method: Participants recruited via local and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The most commonly suggested were the MoCA and the OCS, followed by the ACE and the CAM (Addenbrooke's Cognitive Assessment (Mioshi et al, 2006)and Cognitive Assessment of Minnesota (Rustad et al, 1993)). Key reasons for choosing assessments included speed and ease of use, and familiarity which is consistent with other findings (Ablewhite et al, 2019). The MMSE was only proposed once and for only one vignette, unlike findings by Koh et al (2009) and Korner-Bitensky et al (2011) in which the MMSE was one of the most popular tools reported.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The most commonly suggested were the MoCA and the OCS, followed by the ACE and the CAM (Addenbrooke's Cognitive Assessment (Mioshi et al, 2006)and Cognitive Assessment of Minnesota (Rustad et al, 1993)). Key reasons for choosing assessments included speed and ease of use, and familiarity which is consistent with other findings (Ablewhite et al, 2019). The MMSE was only proposed once and for only one vignette, unlike findings by Koh et al (2009) and Korner-Bitensky et al (2011) in which the MMSE was one of the most popular tools reported.…”
Section: Discussionsupporting
confidence: 70%
“…Korner-Bitensky et al (2011) noted the marked variation in practice between OTs participating in their survey and felt that less emphasis was placed on cognition in community services. Similarly, findings from interviews in the qualitative phase of the present study, (Ablewhite et al, 2019) also showed marked variation in the cognitive screening of stroke survivors by OTs working in the community. It seemed that cognitive assessments were selected based on availability and familiarity rather than evidence for appropriateness to the suspected cognitive problem.…”
Section: Introductionsupporting
confidence: 75%
“…In the audit of dressing (Worthington et al, 2020), we were initially struck by how few (24%) occupational therapists in acute stroke rehabilitation report using standardised outcome measures to evaluate dressing. However, this is perhaps unsurprising given the many factors affecting the use of standardised assessment; among them confidence or training in selection and administration (Ablewhite et al, 2019). The measures themselves may become outdated or lack ecological validity (i.e.…”
Section: How Do They Do This?mentioning
confidence: 99%
“…Cognitive assessment tools designed specifically for stroke populations (e.g. Oxford Cognitive Screen, OCS)8 are increasingly used for this purpose, as well as in community stroke settings 9. Stroke-specific tools, such as the OCS, are usually administered by occupational therapists as a form of first-line screening for cognitive problems after stroke and scores from these assessments are used to inform and plan rehabilitation programmes,9 which may include further referral to clinical neuropsychology services where appropriate.…”
Section: Introductionmentioning
confidence: 99%